Oxovanadium(IV) and ruthenium(II) carbonyl complexes of ONS‐donor ligands derived from dehydroacetic acid and dithiocarbazate: Synthesis, characterization, antioxidant activity, DNA binding and in vitro cytotoxicity. (21st December 2018) - Sarhan, Amira M.; Elsayed, Shadia A.; Mashaly, Mohammad M.; El‐Hendawy, Ahmed M.
Abstract : A series of new complexes of oxovanadium(IV) [VO(L)(B)] and ruthenium(II) [Ru(CO)(PPh3 )2 (L)] (1.1- 1.3, 2.1–2.3 ) (H2 L = dehydroacetic acid Schiff base of S ‐methyldithiocarbazate, H2 smdha (1 ) or S ‐benzyldithiocarbazate, H2 sbdha (2 ); B = 2, 2′‐bipyridine (bpy) or 1, 10‐phenanthroline (phen)) have been synthesized. The structure of these complexes was authenticated using elemental analyses and spectroscopic techniques, and their magnetic properties and electrochemical behaviour were studied. The molecular structures of oxovanadium(IV) complexes [VO(smdha)(bpy)]⋅CH2 Cl2 (1.1 ) and [VO(sbdha)(phen)]⋅2H2 O (2.2 ) were confirmed using single‐crystal X‐ray crystallography. Analytical data showed that the ligands1 and2 are chelated to the metal centres in a bi‐negative tridentate fashion through azomethine N, thiol S and deprotonated hydroxyl group. The antioxidant activity of the synthesized compounds was tested against 2, 2‐diphenyl‐1‐picrylhydrazyl) radical, which showed that the complexes demonstrate a better scavenging activity than their corresponding ligands. The cupric ion reducing antioxidant capacity method was also employed and the total equivalent antioxidant capacity values were found to be higher for the oxovandium(IV) complexes. DNA binding affinity of the compounds was determined using UV–visible and fluorescence spectra, revealing an intercalation binding mode. Higher cytotoxicity for the complexes compared to their ligands was found against human liver hepatocellular carcinoma (HepG2) and breast adenocarcinoma (MCF7) cell lines using MTT assay. Abstract : Highlights Biologically active ligands of dehydroacetic acid and S ‐dithiocarbazate have been prepared. New V(IV) and Ru(II) complexes have been synthesized. Spectroscopic tools and single‐crystal X‐ray crystallography have been used for molecular structure characterization. Antioxidant activity, DNA binding affinity and anticancer activity have been evaluated for the complexes.